ChemInform Abstract: N‐Vinylation and N‐Allylation of 3, 5‐Disubstituted Pyrazoles by N—H Insertion of Vinylcarbenoids. Issue 15 (24th March 2016) - Gill, Agagia; Werz, Udo R.; Maas, Gerhard
Abstract: The rhodium‐catalyzed reactions of methyl styryl‐diazoacetate or dimethyl 2‐diazoglutaconate with the title pyrazoles lead to product mixtures as a result of the regioselectivity issues of the pyrazole or the vinylcarbenoid moiety as well as positional and configurational isomerism due to the C=C double bond of the latter.